Disease-state dependent associations between intrinsic brain function and symptoms of fatigue, depression, and anxiety in Crohn’s disease - Thomann, Anne K.; Schmitgen, Mike; Stephan, Jule C.; Knödler, Laura-Louise; Gass, Achim; Thomann, Philipp; Ebert, Matthias; Reindl, Wolfgang; Wolf, Robert Christian (Inflammatory bowel diseases, 2025)
Extraintestinal symptoms (EIS) in inflammatory bowel diseases, including fatigue, depression and anxiety, are highly prevalent, but poorly understood. Alterations of brain function may contribute to EIS, but their association with disease activity is unclear. This study analyzed intrinsic neural activity (INA) of individuals with Crohn’s disease (CD) in different disease states and examined the relationship between INA and EIS.Patients with CD (n = 92) and healthy controls (n = 41) underwent functional magnetic resonance brain imaging and completed symptom-specific psychometry. Temporal (amplitude of low-frequency fluctuations, ALFF) and spatial (regional homogeneity, ReHo) markers of INA were compared between CD and controls and between active (patients with active Crohn’s disease [aCD]) versus remitted (rCD) disease. Regression analyses explored disease-state-dependent associations between INA and EIS.Patients exhibited aberrant INA in frontotemporal, occipital, and thalamic regions. Patients with aCD exhibited lower ALFF in left subcallosal cortex and inferior temporal gyri compared to rCD. Regional homogeneity in aCD was lower in left medial orbital gyrus and higher in right superior frontal, left inferior temporal, and left precentral gyrus. Compared to rCD, aCD showed higher ALFF predominantly in superior, ventro-, and dorsolateral prefrontal regions. Distinct associations between INA and EIS were detected in patients, particularly in the remitted state.Intrinsic brain function in patients with CD varies by disease state, with prominent frontal cortex changes in active disease. These brain activity changes are at least partly related to the magnitude of neuropsychiatric symptoms and highlight a role of disturbed brain-gut interactions in the development of EIS especially in rCD.This study examined the intrinsic brain function of individuals with Crohn’s disease in different disease states and healthy controls. Brain activity differed between patients and controls and between disease states and correlated with fatigue and depression in remitted disease only.